Brain radiotherapy and dorsal vagal complex irradiation: A new organ at risk to decrease radiation-induced nausea and vomiting? - Valentine Caspar; Nicolas Giraud; Thomas Charleux; Arnaud Beddok; Brieuc Bernard; Maelle Martin; Juliette Thariat; Aymeri Huchet; Véronique Vendrely; Charles Dupin (Clinical and Translational Radiation Oncology)
Purpose: Nausea is a common symptom in patients irradiated for benign brain tumors. The dorsal vagal complex (DVC) located in the brainstem (BS) has been identified as the center of nausea and vomiting. The objective of our study was to determine an association between mean dose to the DVC and nausea. Material: Details of consecutive patients treated for benign brain tumors at the Bordeaux University Hospital using normofractionated intensity modulated radiotherapy technique, without chemotherapy, were accessed. DVC delineation was performed on MRI T1 sequences with gadolinium injection using a reference atlas. Results: Among 102 patients, 68 were women, and median age was 61.5 years. The tumors treated were primarily meningiomas (80 %) and neurinomas (17 %). The median dose was 54 Gy [48.6–57.6 Gy]. In the overall population, 40 (39.2 %) had nausea, requiring anti-nausea treatment for 23 (57.5 %). Patients with nausea were significantly younger (45.5 versus 63.2 years, p = 0.014).For patients without and with nausea, the mean DVC dose was 8.9 Gy versus 21.6 Gy (p < 10-4), respectively, and the mean brainstem dose was 16.9 Gy versus 27.1 Gy (p < 10-3). The optimal threshold for mean DVC dose was 8.82 Gy (AUC = 0.731, p < 10-4). Patients with DVC receiving less than 8.82 Gy had a 16 % risk to have nausea versus 62 % for patients receiving more than 8.82 Gy (p < 10-4). The optimal threshold for mean brainstem dose was 24 Gy (AUC = 0.715p < 0.0001). Conclusion: The mean DVC dose is significantly associated with radiation-induced nausea. A dose constraint below 8.82 Gy to decrease the incidence of radiation-induced nausea needs to be validated by a prospective study.